The importance of promoting oral health in schools: a pilot study - Sabina Saccomanno; Martina De Luca; Stefano Saran; Maria Teresa Petricca; Elena Caramaschi; Rodolfo Francesco Mastrapasqua; Giuseppe Messina; Gianni Gallusi (PAGEPress Publications, 2023)
Promotion of oral health has an essential role in the maintenance of teeth in adults. However, health education must start from an early age, in order to monitor the child's growth and prevent pathologies. Schools are in charge of the overall education of children and of guidance to parents but could also be engaged in the promotion of oral health, supported and counseled by pediatricians and dentists. The purpose of this pilot study is to evaluate whether school age children could be taught, successfully, basic oral sciences and dental hygiene, by a professional, during school hours. In this pilot study, an anonymized test was administered to 45 children of age between 8 and 10, both before and after an interactive lecture on oral health, to assess the effectiveness of the lesson and acquisition by the children of knowledge on oral health. After the presentation, the majority of the children were able to answer correctly to the questionnaire that was given to them (test, retest) which was related to dental anatomy and pathology (number of teeth, cavities, halitosis), and dental hygiene tools and practices (brushes, floss, mouth wash, tongue scrapers). The children seemed to be receptive to learning while in school, and a specific educational session of dental hygiene and oral health seems to be the right approach to ensure children can identify dental hygiene tools and use them appropriately.